а)
б) 5,05
Пошаговое объяснение:
a) 12,1 + 3 - (7,681 + 3,319)
12,1 =
3 =
7,681 + 3,319=11
Общий множитель 10, умножаем 7 на 5 и 11 на 10
=
Сокращаем дробь на 2
(или же можно сделать так: 4
б) 9,7 - 6 + (2,619 - 1,019)
6 =
2,619 - 1,019 = 1,6
9,7 - 6,25 = 3,45
3,45 + 1,6 = 5,05
P.S.: Если не трудно, то можно лучший ответ с:
а)![\frac{23}{5}](/tpl/images/1726/5686/ceb63.png)
б) 5,05
Пошаговое объяснение:
a) 12,1 + 3
- (7,681 + 3,319)
12,1 =![\frac{121}{10}](/tpl/images/1726/5686/74339.png)
3
= ![\frac{7}{2}](/tpl/images/1726/5686/447a9.png)
7,681 + 3,319=11
Общий множитель 10, умножаем 7 на 5 и 11 на 10
Сокращаем дробь на 2
б) 9,7 - 6
+ (2,619 - 1,019)
6
=![\frac{25}{4}](/tpl/images/1726/5686/70ba6.png)
2,619 - 1,019 = 1,6
9,7 - 6,25 = 3,45
3,45 + 1,6 = 5,05
P.S.: Если не трудно, то можно лучший ответ с: